Efecto de Abono foliar líquido (Biol) en el Rendimiento del Arroz (oryza sativa) en San Martín Perú - Montenegro Centurión, Soimer Homero (2006)
The present investigation work, had as objective, to determine the effect of five boil dose in the yield and the quality molinera of the grain of rice (Oriza sativa var. Capirona) in San Martín - Peru in the period of September - 2005 to January - 2006 and to carry out the economic analysis of the treatments. The work was carried out in the District of Cacatachi, county and Region San Martin - Peru, with a Temperature Monthly Average of 27,6 °C.; Relative Humidity of 71,5% and an Accumulated Precipitation of 713,7 mm during the experiment; 1 am accustomed to free loamy and a pH of 6,85. Located in an area of life Tropical Dry forest. The design statistical employee was at random of Complete Blocks, with factorial arrangement of 2 for 7 with 14 treatments and three repetitions. Being that the treatments with more yields are the T10 with 6806,8 Kg/Ha and the T11 with 6799,9 Kg/Ha. With dose of 400 and 500 liters of Biol. (chablor) more 180 nitrogen units for hectare. The biol influence (chablor) in the such parameters as macollas, cobs, days to the floración and maturation, it is not clear however in the quality molinera there is an influence of which bigger grain percentage has been achieved entirely with the biggest biol doses. The biol (Chablor) it is a fertilizer that has to be supplemented with other inorganic fertilizers to complete the elements and it cannot be applied as unique fertilizer because being an organic fertilizer is faulty in the biggest elements mainly of Nitrogen, match and potassium.